Comparative Effectiveness of Best Practice Alerts with Active and Passive Presentations: A Retrospective Study. Issue 1 (September 2020) - Valvona, Sharon N.; Rayo, Michael F.; Abdel-Rasoul, Mahmoud; Locke, Linda J.; Rizer, Milisa K.; Moffatt-Bruce, Susan D.; Patterson, Emily S.
We assess the relationship of active or passive presentation of Best Practice Advisories (BPAs) for hospital clinicians with compliance rates of recommended actions. We identify the design characteristics of alerts that can be used to assess the effectiveness of design choices with superior usability. Alerts in Electronic Health Records (EHRs) are frequently overridden by healthcare providers. Identifying characteristics of effective alerts can increase the frequency that actions recommended in evidence-based care guidelines are done, reduce user frustration, and improve interface usability along with the willingness to use alerts. We conducted a retrospective analysis of data for 11 BPAs between June 2014 and May 2015. The outcome measure was the percent correspondence with recommended actions. A repeated measures regression model was used for the correlation of the BPA presentation type with the outcome measure. The BPA presentation type was significant such that the odds are 7.7 times greater that a recommended action would be taken by a provider with an active BPA presentation type after adjusting for whether an action was required. Active presentation alerts achieve higher compliance rates. CDS alerts that actively interrupted the provider's workflow were associated with a higher compliance rate with recommended actions.